HBV preS2 transactivates FOXP3 expression in malignant hepatocytes. (8th August 2014) - Zhang, Xiaoning; Gao, Lifen; Liang, Xiaohong; Guo, Min; Wang, Rong; Pan, Yingfang; Liu, Peng; Zhang, Feng; Guo, Chun; Zhu, Faliang; Qu, Chunfeng; Ma, Chunhong
Abstract Background & Aims Recent data reported the increased expression of forkhead box protein 3 (FOXP3), the well known master regulator of CD4+C25+ regulatory T cells, in hepatocellular carcinoma (HCC) cells. However, the mechanisms remain unknown. We previously showed that preS2, one of important regulatory proteins encoded by HBV, triggers transactivation of hTERT in malignant hepatocytes. Here, we aimed to explore the role of preS2 in regulating FOXP3 expression in HCC. Methods FOXP3 expression was detected by RT‐PCR, Western blot and immunohistochemical staining. Cotransfection and siRNA knockdown were involved to study the regulation effects of preS2 on FOXP3 expression in cultured HCC cell lines. Luciferase reporter assay and EMSA assay were performed to explore the mechanism of preS2‐mediated FOXP3 upregulation. Results Immunohistochemical staining detected significant increased FOXP3 expression in malignant hepatocytes from sections of HCC patients. The total FOXP3 expression in hepatocytes from patients with HBsAg‐positive HCC was significantly increased compared to that of HBV‐negative HCCs (P = 0.002). In accordance, preS2 overexpression enhanced FOXP3 expression in HCC cell lines, while preS2 knockdown significantly reduced FOXP3 expression in HBV‐integrated HepG2.2.15 cells. Results of cotransfection and luciferase report assay showed that preS2 transactivated FOXP3 promoter in a dose‐dependent manner. Further study identified the AP‐1 binding site at 20 bp region from −465 bp to −445 bp of FOXP3 promoter was responsible for preS2‐induced FOXP3 transcriptional activation. Conclusions Our data here, for the first time, provided direct evidence to demonstrate that preS2 oncoprotein encoded by HBV transactivated FOXP3 transcription in HCC cells.